Job satisfaction of healthcare professionals in two East London public hospitals in South Africa in the context of Covid-19 - Dlodlo, Nkosilathi (University of the Witwatersrand, Johannesburg, 2023)
Introduction: Job satisfaction of healthcare workers is important to provide better patient care and with the prediction by the World Health Organization (WHO) that there would be a shortage of healthcare workers by 2030. The Covid-19 pandemic affected healthcare workers differently and hence the reason for the study. The aim is to explore and understand healthcare workers’ job satisfaction during the Covid 19 pandemic and make recommendations for human resource management to keep healthcare workers satisfied. Methodology: data collection was done from the 10th of October 2022 to the 5th of January 2023, with 203 participants from Cecilia Makiwane Hospital (CMH) and Frere Hospital (FH). Convenience sampling was done through an online survey that compromised of demographic and modified job satisfaction survey questions (JSS). Results: 82% of the participants were dissatisfied with the pay and remuneration; 76% were dissatisfied with supervision from the hospital management, and 83% were dissatisfied with contingent rewards. The healthcare workers were only moderately satisfied with their relationships with co-workers, which had a 41% satisfaction level. Conclusion: there is a need to improve on financial and non-financial components that would then motivate the healthcare workers and inevitably lead to better job satisfaction levels through regular assessment and improved policies that meet the needs of the healthcare workers
A thesis presented in partial fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, 2023
Keywords: UCTD; Job satisfaction; healthcare professionals; public hospitals; South Africa; Covid-19; SDG-8: Decent work and economic growth; SDG-3: Good health and well-being